Towards a kinetic understanding of the ignition of air-propane mixture by a non-equilibrium discharge: the decomposition mechanisms of propane. (1st January 2013) - Pasquiers, Stéphane; Bentaleb, Sabrina; Jeanney, Pascal; Blin-Simiand, Nicole; Tardiveau, Pierre; Magne, Lionel; Gadonna, Katell; Moreau, Nicolas; Jorand, François
The decomposition of propane in non-thermal plasmas of N2 /C3 H8 and N2 /O2 /C3 H8 mixtures (oxygen percentage up to 20%) at low temperature is studied in a photo-triggered discharge. Quenching of nitrogen metastable states dissociate C3 H8 to produce propene and hydrogen. Oxidation reactions are growing in importance when the O2 concentration increases, but the dissociation quenching reactions still occurs for the air-based mixture. Even for a low concentration of oxygen, OH is an important specie involved in the conversion of the hydrocarbon. A kinetic analysis emphasises that OH comes in great part from the production of H, in which the methyl radical plays a role, strengthening the role of the dissociation processes of propane and propene in the medium reactivity. Results of PLIF measurements performed on OH during the diffuse afterglow of a nanosecond corona discharge correlate with results obtained on the photo-triggered discharge.